Electrochemical properties of MnSe inclusions and improving the pitting corrosion resistance of stainless steel via Se microalloying - Masashi Nishimoto; Tomoki Katsuyama; Izumi Muto (Scientific Reports, 2024)
Abstract Controlling the electrochemical properties of non-metallic inclusions is of substantial interest in the design of corrosion-resistant alloys. To the best of our knowledge, the dissolution and pitting corrosion behavior of selenide inclusions in stainless steels and the improvement of the pitting corrosion resistance of type 304 stainless steels via Se microalloying have not been investigated. In this study, stainless steel specimens containing artificial MnS and MnSe inclusions were fabricated via spark plasma sintering to systematically investigate their electrochemical properties. The superior pitting corrosion resistance and dissolution resistance of MnSe to those of MnS were demonstrated. The results obtained from the sintered specimens were applied to improve the pitting corrosion resistance of type 304 stainless steels via Se microalloying. Adding a trace amount of Se (0.005 mass%) altered the readily soluble sulfide inclusions to dissolution-resistant selenide-type inclusions, resulting in improved pitting corrosion resistance of type 304 stainless steel.